Sistem Komunikasi Masyarakat Kepulauan dan Kompleksitas Multi Etnis (Studi Kasus Sistem Komunikasi Masyarakat Kepulauan dan Kompleksitas Multi Etnis di Pulau Sapeken, Kabupaten Sumenep, Madura) - Tatag Handaka (LUGAS Jurnal Komunikasi, 2018)
The society of Sapeken islands are multi ethnic society. They’re multicultural society. The aim of the research is to know about Sapeken’s society communication system to encounter multi ethnic complexities. The theory of the research is communication system in Niklas Luhmann perspective. The research used case study method. The result of the research shown that society communication system has produced and reproduced information to encounter environmental complexities about multi ethnic. Information which produced by system are collective fish selling, collective purchasing foods and beverages, and religious activities. Information which produced by society communication system was effective to solve multi ethnic complexities. Government communication system have not produced information related to multi ethnic complexities.